A case study on the public relations of Bulacan Provincial Library - Esguerra, Ma. Carmela C. (1999)
Public relations is one aspect of librarianship that is always taken for granted by many libraries particularly the public ones. Thus, the purpose of this study was to discover how the Bulacan Provincial Library promotes itself and how effective its strategies are, since it is the biggest public library that exists in the province of Bulacan with rich collections and services offered to its clientele and to other residents of Bulacan.